The Effect of Financial Knowledge, Perceived Trust and Perceived Use on Interest in Using Shopee Paylater - Bachtiar, Sonia; Yuli kartika; Salsabila, Shafa Tasya (Jurnal Manajemen Bisnis, 2024)
With the increasing interest in online shopping in Indonesia, there are more options for online transaction payments. One of them is ShopeePay later. This study aims to find the relationship and impact of financial knowledge, perceived trust, and perceived use on intention to use Shopee Paylater in generation Z in Indonesia. The research method uses a quantitative approach with a research sample of 231 people of generation Z in Java. The collected data was tested using the SEM-PLS technique through SmartPLS 4.0 software. The test results show that financial knowledge has a positive and significant effect on Shopee Paylater's perceived trust. Then perceived trust and perceived use have a positive and significant effect on interest in using Shopee Paylater. However, financial knowledge variables have no significant effect on the perceived use and interest of Shopee Paylater. The results of this study are expected to help and provide positive benefits for people who read about and want to research Shopee Paylater.